2014
DOI: 10.1007/s00424-014-1534-y
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-induced relaxation involves L-type and store-operated Ca2+ channels blockade, and PGE2 in guinea pig airway smooth muscle

Abstract: In vascular smooth muscle, it has been described that testosterone (TES) produces relaxation by blocking L-type Ca(2+) channels. Recently, we found that L-type Ca(2+) and store-operated Ca(2+) (SOC) channels are the main membranal structures that provide extracellular Ca(2+) for carbachol (CCh)-induced contraction in airway smooth muscle (ASM). We studied the possible interactions between L-type and SOC channels in TES-induced relaxation in guinea pig ASM. TES (10, 32, 100, and 178 μM) induced a complete relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Therefore, Ca 2+ sensitization by RhoA/Rho-kinase processes [1,173,174,175] and Ca 2+ dynamics by ion channels including VDC and SOC [6,11,12,176] may be a therapeutic target for obstructive pulmonary diseases including asthma.…”
Section: Interaction Between Airway Smooth Muscle and Inflammatory Cellsmentioning
confidence: 99%
“…Therefore, Ca 2+ sensitization by RhoA/Rho-kinase processes [1,173,174,175] and Ca 2+ dynamics by ion channels including VDC and SOC [6,11,12,176] may be a therapeutic target for obstructive pulmonary diseases including asthma.…”
Section: Interaction Between Airway Smooth Muscle and Inflammatory Cellsmentioning
confidence: 99%
“…ACh, a muscarinic receptor agonist, can activate both VDLCCs and NSCCs, which induce Ca 2+ influx and cause ASM contraction [19][20][21][22]. Our results demonstrated that nuciferine also relaxed ACh-contracted ASMs in a dose-dependent manner, which suggested that nuciferine could also inhibit all NSCCs except VDLCCs.…”
Section: Discussionmentioning
confidence: 51%
“…ACh elicited a contraction in TRs by activating the muscarinic receptor and its downstream signaling pathways [19][20][21][22], which differ from the pathway activated by high K + . To further elucidate the mechanisms of nuciferine-induced relaxation, we explored the effects of nuciferine on ACh-contracted TRs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After its emptying, the SR Ca 2+ refilling seems to involve increases in Na + concentrations in sites nearby. This refilling is also related to smooth muscle sustained contraction (1218). Recent findings in our laboratory, demonstrate that Na + permeates through the L-type voltage dependent Ca 2+ channels when ASM is stimulated with carbachol (19).…”
Section: Introductionmentioning
confidence: 98%